The impact of colonisation on te reo Māori: A critical review of the State education system - Ka'ai-Mahuta, Rachael (Te Kaharoa, 2011)
By 1979, merely 139 years after the signing of Te Tiriti o Waitangi (The Treaty of Waitangi), the loss of te reo Māori was so great that it was believed it would suffer language death (Walker 1990: 147-148). This can be attributed to colonisation and the State policy of assimilation which eroded the status of the language. The mechanism of the Government’s agenda of assimilation and language domination was the State education system. This was, therefore, the primary cause of Māori language loss. In some cases the legislation regarding the State education system can be directly linked to language loss. However, in many cases the education system has negatively affected te reo Māori indirectly through aspects of Eurocentric education. These include assimilation, cultural invasion, cultural subordination, language domination, hegemony, the curriculum, class structures, racism, meritocracy, intelligence testing, and negative teacher expectations. In the study of Māori language decline one must critically review the New Zealand State education system, including a discussion of the key events and legislation in the history of Pākehā colonisation and assimilation in Aotearoa/New Zealand. This will form the chronological map of the deterioration of the status of the Māori language.